The occurrence of bleached topsoils on weakly structured subsoil horizons in the Western Cape and Mpumalanga Provinces of South Africa - Le Roux, Johannes Lukas (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.